Potential predictors of lower extremity impairments in motor coordination of stroke survivors - Menezes, Kenia K. P.; Scianni, Aline A.; Faria-Fortini, Iza; Avelino, Patrick R.; Carvalho, Augusto C. [UNESP]; Faria, Christina D. C. M. [UNESP]; Teixeira-Salmela, Luci F. [UNESP] (Edizioni Minerva Medica, 2016)
BACKGROUND: It is well recognized that the negative motor impairments following upper motor neuron damage, e.g., loss of strength and dexterity (motor coordination), mostly contribute to disability. Many factors may predict impairments in motor coordination (MC) and the identifications of these factors could help rehabilitation professionals to select variables to be considered in the evaluation and interventions aimed at improving MC of the lower limbs after stroke. AIM: To investigate the potential predictors of motor coordination (MC) of the paretic lower limb with stroke subjects, as assessed by the Lower Limb Motor Coordination Test (LEMOCOT). DESIGN: Cross-sectional, observational study. SETTING: University laboratory. POPULATION: One hundred and six stroke subjects. METHODS: The selected potential predictors of the LEMOCOT scores were age, gender, motor recovery and sensation of the lower limb, tonus of the knee extensor and plantar flexor muscles, and strength of the hip flexor and knee flexor/extensor muscles. Step-wise multiple regression was employed for analysis. RESULTS: Only motor recovery, tonus of the plantar flexor muscles, and age reached significance (P<0.05) and, consequently, were kept in the model. Motor recovery alone was able to explain 46% (F=89.0, P<0.001) of the variance in the LEMOCOT scores. When tonus of the plantar flexor muscles and age were included in the model, the explained variance increased to 54% (F=42.0, P<0.001). Lower limb motor recovery was positively associated with the LEMOCOT scores, whereas the tonus of the plantar flexor muscles and age were negatively correlated. CONCLUSION: Motor recovery of the lower limb, tonus of the plantar flexor muscles, and age were significant predictors of MC of the paretic lower limb. CLINICAL REHABILITATION IMPACT: These findings could help rehabilitation professionals to evaluate MC deficits and plan interventions aimed at improving MC of the lower limbs for stroke subjects, based upon the knowledge of the possible factors that could contribute to MC impairments.
Keywords: Motor skills; Lower extremity; Stroke